Improving dissolution and oral bioavailability of pranlukast hemihydrate by particle surface modification with surfactants and homogenization - Ha ES; Baek I; Yoo JW; Jung Y; Kim MS (Dove Medical Press, 2015)
Eun-Sol Ha,1 In-hwan Baek,2 Jin-Wook Yoo,1 Yunjin Jung,1 Min-Soo Kim1 1College of Pharmacy, Pusan National University, 2College of Pharmacy, Kyungsung University, Busan, Republic of Korea Abstract: The present study was carried out to develop an oral formulation of pranlukast hemihydrate with improved dissolution and oral bioavailability using a surface-modified microparticle. Based on solubility measurements, surface-modified pranlukast hemihydrate microparticles were manufactured using the spray-drying method with hydroxypropylmethyl cellulose, sucrose laurate, and water and without the use of an organic solvent. The hydrophilicity of the surface-modified pranlukast hemihydrate microparticle increased, leading to enhanced dissolution and oral bioavailability of pranlukast hemihydrate without a change in crystallinity. The surface-modified microparticles with an hydroxypropylmethyl cellulose/sucrose laurate ratio of 1:2 showed rapid dissolution of up to 85% within 30 minutes in dissolution medium (pH 6.8) and oral bioavailability higher than that of the commercial product, with approximately 2.5-fold and 3.9-fold increases in area under the curve (AUC0→12 h) and peak plasma concentration, respectively. Therefore, the surface-modified microparticle is an effective oral drug delivery system for the poorly water-soluble therapeutic pranlukast hemihydrate. Keywords: solubility, wettability, sucrose laurate, cellulose